Cancer Immunotherapy & Immuno-monitoring: Mechanism, Treatment, Diagnosis, and Emerging Tools - Chao Ma; Antoni Ribas; Rong Fan (Frontiers Media SA, 2014)
In the past decade, significant progresses have taken place in the field of cancer immunotherapy. Tumor-targeting immunotherapies are being developed for most human cancers, including melanoma, prostate cancer, glioblastoma, sarcoma, lung carcinoma and hepatocellular carcinoma. The FDA has approved multiple molecular immunotherapeutics, such as Ipilimumab; cellular immunotherapies (e.g. adoptive cell transfer) are being tested in phase II/III clinical trials. Immunotherapetics has evolved into a sophisticated field: Multimodal therapeutic regimens are administrated to induce focused responses, curtail side- effects and improve therapeutic efficacy. The lack of effective clinical assessment tools remains a major challenge. Because of the intricacy of antitumor response, it is essential to scrutinize individual tumor-targeting immune cells and their functions at the finest details - molecules. In this regard, flow cytometry analysis modernized hematology and allows characterization of surface molecular signature on individual cells. More recently, microchip technologies and new variations of cytometry have enormously expanded the spectrum, throughout and multiplexity of single cell analysis. Nowadays, tens of millions of readouts can be generated through the course of a cancer immunotherapy to monitor the abundance, phenotype and a myriad of effector functions of single immune cells. At the same time, big data analytics and data mining methodologies have been adapted to achieve sensible diagnostic interpretations. Such a marriage of technology and analytics opens the door for informative point-of-care assessment of therapeutic efficacy and ensures timely therapeutic decisions. The new generation of personalized clinical diagnostics will revolutionize healthcare in the years to come.
English
Keywords: immune assessment; single cell analysis; cancer immunotherapy; tumor immunity; immune suppression